TEKNIK DAN FUNGSI PENERJEMAHAN KATA UMPATAN PADA NOVEL RIḤLAH ILĀ ALLĀH - Baking, Aad Nur Sayyidus Syuhuur; Sajarwa, Sajarwa (Adabiyyāt: Jurnal Bahasa dan Sastra, 2023)
This study aims to find out the translation techniques of swear words in the novel Riḥlah ilā Allāh by Najib Kaelani and the function of those swear words. The data in this study are in the form of swear words and their translations which are sourced from the novel Riḥlah ilā Allāh and its translation "Meniti Jalan Allah". The used theory for this research is the translation techniques from Molina & Albir’s perspectives, and Swear words functions by Trudgill & Andersson. This research is descriptive and qualitative with the data collection method using the reading and note-taking method. Furthermore, the data analysis technique starts by grouping the data, looking for the techniques used in translating swear words, then determining the function of the swear words that have been collected. The results showed that the swear words in the novel Riḥlah ilā Allāh by Najib Kailani were translated using eight techniques, and have three functions, namely expletive, abusive, and auxiliary.